The National Consensus Formation at the First Stage of Russia’s Special Military Operation Against Ukraine (February–August 2022) - Ivan Krivushin; Marina Glaser (Journal of Eurasian Studies)
The article begins with a definition of some contesting views about the reality of Russian support for the “Special military operation” (SMO), hypotheses, and research approach. Then we present the substantive arguments about the attitude of Russian residents to the SMO and the reliability of public opinion polls results. After this we provide suggestive analyzes of three key understandings of the “West” in Russian public opinion. The article ends with arguing that a national consensus in Russia on the necessity and legitimacy of the SMO has really been achieved. The polarization of opinions is increasing but it is not reflected in the public sphere because of the fears that this could cause negative uncontrolled consequences for the economic situation, social and political stability in the country. As for Anti-Western sentiments, they depended and continue to depend on two groups of factors: foreign policy ones, which provoked the strengthening of these sentiments, and internal ones, which contributed to their weakening.